Cognitive Flexibility in Learning Mathematics Senior High School - Zulkarnain, Rezkie; Kurniawan, Apri; Lisarani, Varetha (STKIP Singkawang, 2023)
Cognitive flexibility in learning mathematics is necessary to solve problems with various mathematical ideas. In completing assignments, students have different perspectives so as to bring up creative solutions that encourage problem-solving skills. This study aims to determine students' cognitive flexibility level in high school mathematics learning. This quantitative descriptive research aims to describe the contents of a variable in research, without being intended to test a particular hypothesis. The source of data used in this study was class XI students in Pontianak City totaling 173 people. Data is collected by questionnaire with data analysis calculating the percentage index results of questionnaire answers. Based on the results of the questionnaire categorizing the level of cognitive flexibility ability of students in learning mathematics, it was found that there were 39 students with the category